Zdravljenje avtoimunskih citopenij po alogenični presaditvi krvotvornih matičnih celic - prikaz dveh primerov - Preložnik-Zupan, Irena (Zdravniški vestnik, 2004)
Background. Autoimmune cytopenias, thrombocytopenia, anemia and neutropenia, are rare but serious complications after stem cell transplantation (SCT). There are only a few reports concerning their treatment. We performed splenectomy in two patients with severe autoimmune cytopenias after allogeneicSCT resistant to immunosuppressive treatment. Patients, methods and results. First patient had unrelated alloSCT at Royal Free Hospital London forchronic granulocytic leukemia (CGL) in July 2000. Post-transplant period was complicated with cytomegalovirus reactivation and septicemia. Seven monthslater RBC and platelet counts went dawn. Direct Coomb's test was intermittently positive. She was resistant to steroids and high dose immunoglobulin. Splenectomy was performed in February 2001. After splenectomy hemoglobin concentration and platelet count improved. Her blood counts remained stable with hemoglobin about 110 g/L and platelets over 100 x 10 9/L.She continued therapy with Itraconazol, Valacyclovir and Penicillin. Threemonths later she was readmitted for E. Coli fulminated septic infection with fatal outcome. Second patient had related alloSCT at University Medical Centre Ljubljana for CGL in January 2003. Past-transplant course was uneventful. Seven months later he was readmitted for retinal bleeding with severe thrombocytopenia with positive anti-platelet antibodies. He was resistant to steroids and high dose inamunoglobulin. Splenectomy was performedin September 2003. His platelet count normalized and remains stable so far. He continues therapy with Itraconazol, Valacyclovir and Penicillin anddidn't experience any serious infection. Conclusions. We assume that splenectomy is an efficient treatment for resistant immune cytopenias after alloSCT. However, severe late infections may compromise the outcome.
Keywords: Adverse Effects; Anemia, Hemolytic; Anemija hemolitična; Hematopoetska matična celica, presaditev; Hematopoietic Stem Cell Transplantation; Neutropenia; Nevtropenija; Platelet Count; Splenectomy; Splenektomija; Thrombocytopenia; Trombociti, štetje; Trombocitopenija